2021
DOI: 10.3390/ijms22073491
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Structural Changes of Polylactide and Poly(ethylene terephthalate) in the Presence of Trichoderma viride

Abstract: Plastic pollution is one of the crucial global challenges nowadays, and biodegradation is a promising approach to manage plastic waste in an environment-friendly and cost-effective way. In this study we identified the strain of fungus Trichoderma viride GZ1, which was characterized by particularly high pectinolytic activity. Using differential scanning calorimetry, Fourier-transform infrared spectroscopy techniques, and viscosity measurements we showed that three-month incubation of polylactide and polyethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 94 publications
(54 reference statements)
0
9
0
Order By: Relevance
“… Nepenthes ampullaria Malaysia PU Zone of clearance in medium after 2–3 weeks of incubation Lii et al ( 2017 ) Clonostachys rosea , Trichoderma sp. Arctic soil Norway PCL Weight loss, morphological changes Urbanek et al ( 2017 ) Candida tropicalis Culture Malaysia LDPE, SBP Weight loss, morphological changes, biofilm formation Zahari et al ( 2021 ) Trichoderma viride GZ1 NM Poland PLA, PET Hydrophobin production, chemical and morphological changes after 3 months of incubation Dąbrowska et al ( 2021 ) Absidia sp., Actinomucor elegans , Aspergillus fumigatus, Aureobasidium pullulans, Bjerkandera adusta, Cladosporium subcinereum, Fusarium sp., Mortierella sp., Penicillium sp., Trichoderma harzianum Agricultural soil Slovakia PLA, PHB and PLA/PHB blend polymers Weight loss after 1 year of mineralization Jeszeová et al ( 2018 ) Engyodontium album MTP091 (SF1), Pencillium sp. MTP093 (SF3), Phanerochaete chrysosporium NCIM 1170 (SF2) Soil ( E. album , Pencillium sp.…”
Section: Fungi: a Major Recycler In The Environmentmentioning
confidence: 99%
“… Nepenthes ampullaria Malaysia PU Zone of clearance in medium after 2–3 weeks of incubation Lii et al ( 2017 ) Clonostachys rosea , Trichoderma sp. Arctic soil Norway PCL Weight loss, morphological changes Urbanek et al ( 2017 ) Candida tropicalis Culture Malaysia LDPE, SBP Weight loss, morphological changes, biofilm formation Zahari et al ( 2021 ) Trichoderma viride GZ1 NM Poland PLA, PET Hydrophobin production, chemical and morphological changes after 3 months of incubation Dąbrowska et al ( 2021 ) Absidia sp., Actinomucor elegans , Aspergillus fumigatus, Aureobasidium pullulans, Bjerkandera adusta, Cladosporium subcinereum, Fusarium sp., Mortierella sp., Penicillium sp., Trichoderma harzianum Agricultural soil Slovakia PLA, PHB and PLA/PHB blend polymers Weight loss after 1 year of mineralization Jeszeová et al ( 2018 ) Engyodontium album MTP091 (SF1), Pencillium sp. MTP093 (SF3), Phanerochaete chrysosporium NCIM 1170 (SF2) Soil ( E. album , Pencillium sp.…”
Section: Fungi: a Major Recycler In The Environmentmentioning
confidence: 99%
“…Previous studies and reports have indicated the role and mechanism of action of Trichoderma spp. in the degradation of multiple polymers, such as polycaprolactone, polyethylene terephthalate, polylactide and even chitosan-based films modified with tannic acid, ferulic acid and gallic acid [ 16 , 17 , 18 , 19 , 20 ]. However, polymers with newer and more beneficial modifications are continuously being developed and need to be tested for biodegradation before their application.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer degradation is a complex process involving physical, chemical, and biological factors [9]. Undoubtedly, microorganisms producing hydrolytic enzymes contribute to their biodegradation [8,[10][11][12]]. Fungi, for example, Pseudozyma japonica Y7-09 and Trichoderma viride 99, degraded polycaprolactone (PCL) [13,14], Clitocybe sp.…”
Section: Introductionmentioning
confidence: 99%
“…belong to the Ascomycota, which are the most numerous species of fungi in almost all temperate and tropical soils. They are characterized by rapid growth, abundant sporulation, and the production of several hydrolytic enzymes [11,19].…”
Section: Introductionmentioning
confidence: 99%